Desa Sebapo 1984 – 2010 - Fauziah Maharani, Elsa; Yanto, Ferry; Azmi, Ulul (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
This research discusses the development of Sebapo Village, located in Mestong Subdistrict, Muaro Jambi Regency, since its establishment in 1984 until 2010.in 1984 until 2010. The main focus of this research is to analyze factors that support the development of the village, such as the role of natural resources, community involvement, and government support. Sebapo Village experienced significant increase in infrastructure development after becoming part of Muaro Jambi Regency in 1999. The government's role in counseling the family planning program family planning (KB) program also had an impact on reducing the population growth rate in the village. population growth rate in the village. In addition, this study highlights the potential of the local economy, including the Sebapo Market and Sebapo Nature tourism, which contributed to the village's economic growth of the village. Despite challenges such as the decline in the price of rubber commodity prices and climate change, the Sebapo Village community has successfully adapted by diversifying their economy through oil palm plantations and the tourism sector. tourism sector. This research uses the historical method to reconstruct past events through the stages of heuristics, criticism, interpretation, and historiography. This research is expected to provide contribute to the literature on rural development in Indonesia and become a reference in the development of sustainable development policies. be a reference in the development of sustainable development policies development policy in the village.